2021
DOI: 10.1186/s12913-021-07363-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in patient activation following cardiac rehabilitation using the Active+me digital healthcare platform during the COVID-19 pandemic: a cohort evaluation

Abstract: Background Restrictions on face-to-face contact, due to COVID-19, led to a rapid adoption of technology to remotely deliver cardiac rehabilitation (CR). Some technologies, including Active+me, were used without knowing their benefits. We assessed changes in patient activation measure (PAM) in patients participating in routine CR, using Active+me. We also investigated changes in PAM among low, moderate, and high risk patients, changes in cardiovascular risk factors, and explored patient and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The number of participants ranged from 5 [ 28 ] to 2331 [ 17 ]. The number of participants who did not complete the study ranged from 0 [ 26 , 44 , 52 , 57 , 66 ] to 150 [ 58 ] participants, translating to an incompletion rate of 0% to 92.6%. Three studies did not report a dropout rate [ 37 , 19 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The number of participants ranged from 5 [ 28 ] to 2331 [ 17 ]. The number of participants who did not complete the study ranged from 0 [ 26 , 44 , 52 , 57 , 66 ] to 150 [ 58 ] participants, translating to an incompletion rate of 0% to 92.6%. Three studies did not report a dropout rate [ 37 , 19 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cardiac telerehabilitation has the potential to increase the low CR participation rate in Japan. 14 , 15 In the UK, nearly half of all CR programs have been suspended due to COVID-19 restrictions. Technology was rapidly adopted by CR services; this may increase participation beyond COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…18 Some studies looking at different interventions like online programmes or walking interventions over a period of time showed that patient activation may be changeable. [19][20][21] Thus, there are many studies reporting the association of patient activation with clinical outcomes and healthrelated behaviour. Therefore, it would be helpful to identify which aspects that can be directly addressed by primary care physicians are linked to higher patient activation.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“… 18 Some studies looking at different interventions like online programmes or walking interventions over a period of time showed that patient activation may be changeable. 19–21 …”
Section: Introductionmentioning
confidence: 99%